MANAJEMEN KESISWAAN DI SMK MANBAUL MA’ARIF DESA TAMBAK KECAMATAN LANGGAM KABUPATEN PELALAWAN - SYAFARUDDIN SYAFARUDDIN; HASNAH FAIZAH AR; AZHAR AZHAR (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2017)
This research is qualitative research. The purpose of this research is getinformation about the student’s management system in SMK Manbaul Ma’arif, Tambak,Langgam Dictrict Pelalawan regency. This research focus on describes of student’s managementstudent in SMK Manbaul Ma’arif with subfocus is about : 1) The selection of the new studentin SMK Manbaul Ma’arif 2) to construct the extracurricular in SMK Manbaul Ma’arif. Thedata collection of the first sub focus in this research done by interview and the documentationand the second sub focus done by interview, documentation and observation. The result of thisresearch indicate that the student’s management system in SMK Manbaul Ma’arif done wellbased on sub focus of this research, althought in a few item is still found the problems but it isnot influence of the school aimed to give the best things to their students.